Peningkatan Kualitas UMKM dalam Menghadapi Pasar Bebas - Sugiono, Sugiono (Program Studi Pendidikan Ekonomi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
Small Micro and Medium Enterprises (SMEs) have a strategic role in national economic development. SMEs also play a role in economic growth and employment as well as income distribution. Entering the free market, there should be a special concern for the survival of SMEs in order to survive amid global competition. For that we need a strategic effort in conducting quality improvement of SMEs. Efforts could be done by strengthening the Network of Partnership, Innovation, Technology, Strengthening human capital and Entrepreneurship, Infrastructure Development of Physical Existence of Large Corporations and Access to Markets and Market Information and Access Business Support Services.